Tracing evolutionary decoupling of oral and pharyngeal jaws in cichlid fishes. Issue 6 (1st December 2021) - Ronco, Fabrizia; Salzburger, Walter
Abstract: Evolutionary innovations can facilitate diversification if the novel trait enables a lineage to exploit new niches or by expanding character space. The elaborate pharyngeal jaw apparatus of cichlid fishes is often referred to as an evolutionary "key innovation" that has promoted the spectacular adaptive radiations in these fishes. This goes back to the idea that the structural and functional independence of the oral and pharyngeal jaws for food capturing and food processing, respectively, permitted each jaw type to follow independent evolutionary trajectories. This "evolutionary decoupling" is thought to have facilitated novel trait combinations and, hence, ecological specialization, ultimately allowing more species to coexist in sympatry. Here, we test the hypotheses of evolutionary decoupling of the oral and pharyngeal jaws in the massive adaptive radiation of cichlid fishes in African Lake Tanganyika. Based on phylogenetic comparative analyses of oral jaw morphology and lower pharyngeal jaw shape across most of the ∼240 cichlid species occurring in that lake, we show that the two jaws evolved coupled along the main axes of morphological variation, yet most other components of these trait complexes evolved largely independently over the course of the radiation. Further, we find limited correlations between the two jaws in both overall divergence and evolutionary rates. Moreover, we show that the two jaws were evolutionary decoupled at a late stage of the radiation, suggesting that decoupling contributed to micro-niche partitioning and the associated rapidly increasing trophic diversity during this phase.